Salicylic Acid-Induced Expression Profiles of LRR and LRR-RLK Candidate Genes Modulate Mungbean Yellow Mosaic India Virus Resistance in Blackgram and Its Two Wild Non-Progenitors - Mansi Shukla; Priyanka Kaundal; Shalini Purwar; Mukul Kumar; Chandragupt Maurya; Chirag; Awdhesh Kumar Mishra; Kwang-Hyun Baek; Chandra Mohan Singh (Plants)
Blackgram is an important short-duration grain legume, but its yield is highly affected by various stresses. Among biotic stresses, yellow mosaic disease (YMD) is known as a devastating disease that leads to 100% yield loss under severe conditions. The cultivated lines possess resistance, but exploring more diverse sources of resistance may be useful for pyramiding to improve the durability of said resistance. Some wild Vigna species have potentially demonstrated a high level of resistance. R-genes, including gene families of leucine-rich repeats (LRRs) and leucine-rich repeat receptor-like kinases (LRR-RLKs), are known for modulating the resistance in plants against various biotic stresses. The first comprehensive analysis of the LRR and LRR-RLK gene families in mungbean is reported in the present study. A total of forty-six candidate genes were identified and grouped into eight clades. Protein motif analysis showed that the “Pkinase domain” and “LRR domains” were conserved in most of the R-proteins. The expression of candidate genes viz. VrNBS_TNLRR-8, VrLRR_RLK-20, VrLRR_RLK-17, and VrLRR_RLK-19 demonstrated significantly up-regulated expression upon YMD infection in control and salicylic acid-primed (SA-primed) plants. The analysis provides insight into the diversity and robust candidate genes for functional studies modulating YMD resistance altered by salicylic acid.